Emended description of the South American genus Elephantomene (Menispermaceae) - de Sousa, Julio Dos Santos; Gurgel, Ely Simone Cajueiro (Phytotaxa, 2023)
Elephantomene is a monospecific genus, distributed in South America. To our knowledge, there are no studies about the pistillate flower in Elephantomene eburnea. This is the first complete taxonomic description involving all floral whorls of staminate and pistillate flowers. Between January 2018 and October 2021, including types housed at 32 national and foreign herbaria. In the Neotropics, the Amazonian is the main center of concentration for the genus. The tripartite gynophores, the internal sepals fused forming a solid column and the stamens inserted in this column were the main characters used to identify the species. Descriptions and illustrations of the species are presented, as well as data concerning geographical distribution and additional comments of the species.